Frequency of Megaloblastic Anemia with Thrombocytopenia in Pregnant Patients at Tertiary Care Hospital Karachi - Bibi, Takasur; Khan, Shagufta; Rehman, Memoona; Ali, Sania; Ahmed, Amber (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of megaloblastic anemia with thrombocytopenia in pregnant patients at Tertiary Care Hospital, Karachi. Study Design and Setting: This cross sectional study was conducted at the Department of Gynecology and Obstetrics, JPMC, Karachi from June 2024 to December 2024. Methodology: This cross-sectional study was conducted after approval of a synopsis from the Research Department of the College of Physicians and Surgeons Pakistan and the institutional ethical review committee. Eligible patients at the Department of Gynaecology and Obstetrics, JPMC, Karachi, who meet the inclusion and exclusion criteria were enrolled in the study. Study was completed from June 2024 to December 2024 .All the findings of variables such as age, occupational status, parity, gravida, gestational age, educational status, chicken and beef consumption, vegetable consumption, serum hemoglobin, serum folic acid, vitamin B12, platelets, and megaloblastic anemia were noted. Results: In this study, patients with megaloblastic anemia with thrombocytopenia had a mean age of 27.51±6.18, gestational age of 33.46 ± 4.41, 22% were primipara and 78% were multipara, vitamin B12 deficiency was found in 36.6%, 46.3% were primi-gravid, 53.7% were multi gravida, MCV was 94.58±4.79, serum Hb 12.39 ± 1.07, platelet 117.22 ± 8.55, folic acid deficiency was observed in 80%, occupationally 46.3% were employed and 53.7% unemployed, and 36.6% were illiterate. It’s reassuring to note that the consumption of green leafy vegetables was equally distributed among patients with megaloblastic anemia and those without. Conclusions: This study reveals 18.5% of pregnant women had megaloblastic anemia with thrombocytopenia. This study illustrates that severe megaloblastic anemia and thrombocytopenia caused by dietary deficiencies, such as folic acid and vitamin B12, have a favorable prognosis when correctly diagnosed and treated.